Natural killer cells: a future star for immunotherapy of head and neck squamous cell carcinoma - Dong, Shuyan; Zhao, Ming; Zhu, Jin; Li, Ting; Yan, Mingze; Xing, Kaixun; Liu, Peng; Yu, Shan; Ma, Jian; He, Hongjiang (Frontiers in Immunology, 2024)
The interplay between immune components and the epithelium plays a crucial role in the development and progression of head and neck squamous cell carcinoma (HNSCC). Natural killer (NK) cells, one of the main tumor-killing immune cell populations, have received increasing attention in HNSCC immunotherapy. In this review, we explore the mechanism underlying the interplay between NK cells and HNSCC. A series of immune evasion strategies utilized by cancer cells restrict HNSCC infiltration of NK cells. Overcoming these limitations can fully exploit the antineoplastic potential of NK cells. We also investigated the tumor-killing efficacy of NK cellbased immunotherapies, immunotherapeutic strategies, and new results from clinical trials. Notably, cetuximab, the most essential component of NK cell-based immunotherapy, inhibits the epidermal growth factor receptor (EGFR) signaling pathway and activates the immune system in conjunction with NK cells, inducing innate effector functions and improving patient prognosis. In addition, we compiled information on other areas for the improvement of patient prognosis using anti-EGFR receptor-based monoclonal antibody drugs and the underlying mechanisms and prognoses of new immunotherapeutic strategies for the treatment of HNSCC.